Alpheus S. Bloomfield papers - Bloomfield, Alpheus S.
Typescript letters to Bloomfield's family describing his Civil War service with Battery A of the First Ohio Artillery Regiment in Kentucky, Tennessee, Alabama, and Georgia; preceded by two introductory notes by his son Lloyd Morris Bloomfield, and followed by notes relating to Alpheus S. Bloomfield and Battery A.
Microfilm and enlargement prints produced from originals with permission of Charles A. Bloomfield.
Soldier.
Collection material in English.
Keywords: Bloomfield, Lloyd Morris; United States. -- Army. -- Ohio Light Artillery Regiment, 1st (1861-1865). -- Battery A; Alabama -- History -- Civil War, 1861-1865.; Georgia -- History -- Civil War, 1861-1865.; Kentucky -- History -- Civil War, 1861-1865.; Tennessee -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; Soldiers